Full service : my adventures in Hollywood and the secret sex lives of the stars - Bowers, Scotty, 1923-; Friedberg, Lionel (New York, N.Y. : Grove Press, 2012)
The wholesome image of America propagated by Hollywood in the 1940s, '50s and '60s is one of the most persistent in popular culture: loving wives, smiling children. But off the set, many of the actors who helped create this image were secretly leading very wild lives, and one man in particular was helping them: Scotty Bowers. At a time when sex outside of marriage was taboo, Scotty built up a reputation as the guy who could discreetly fix you up. Scotty slept with many stars himself, and connected others with his friends. Here, he tells his story for the first time. Scotty came to Hollywood after serving in the Marines in World War II, and began working at a gas station on Hollywood Boulevard. One day, he was approached and picked up by actor Walter Pidgeon, who whisked him off to a friend's villa for the first of many encounters with Hollywood's rich and famous. He developed long-term friendships with stars like Katharine Hepburn and Noel Coward, but he always kept it quiet--until he now provides a lost chapter in the history of the sexual revolution.--From publisher description.
Dream factory -- Gas station on Hollywood Boulevard -- Awakenings -- Full service -- Big city -- Star treatment -- turning tricks -- Boot camp -- Into battle -- Firmament of stars -- Vice squad -- Paternity --Mixing drinks -- A royal affair -- At the crossroads -- Moving on -- Myths -- Bar service -- Finding out -- Close encounters of every kind -- To each his own -- The young and the restless --In high places -- Drag queens and music -- True love -- Friends -- The Seventies -- Kew Drive -- Looking back.
Keywords: HOMBRES PROSTITUTOS -- LOS ANGELES -- BIOGRAFIA; PELICULAS CINEMATOGRAFICAS -- PRODUCTORES Y DIRECTORES -- LOS ANGELES -- CALIFORNIA; ACTORES Y ACTRICES DE CINE -- CONDUCTA SEXUAL -- CALIFORNIA -- LOS ANGELES